Buckling Behavior of Sandwich Cylindrical Shells Covered by Functionally Graded Coatings with Clamped Boundary Conditions under Hydrostatic Pressure - Sofiyev, Abdullah H.; Fantuzzi, Nicholas; Ipek, Cengiz; Tekin, Gulcin (MDPI, 2022)
The buckling behavior of sandwich shells with functionally graded (FG) coatings operating under different external pressures was generally investigated under simply supported boundary conditions. Since it is very difficult to determine the approximation functions satisfying clamped boundary conditions and to solve the basic equations analytically within the framework of first order shear deformation theory (FOST), the number of publications on this subject is very limited. An analytical solution to the buckling problem of FG-coated cylindrical shells under clamped boundary conditions subjected to uniform hydrostatic pressure within the FOST framework is presented for the first time. By mathematical modeling of the FG coatings, the constitutive relations and basic equations of sandwich cylindrical shells within the FOST framework are obtained. Analytical solutions of the basic equations in the framework of the Donnell shell theory, obtained using the Galerkin method, is carried out using new approximation functions that satisfy clamped boundary conditions. Finally, the influences of FG models and volume fractions on the hydrostatic buckling pressure within the FOST and classical shell theory (CT) frameworks are investigated in detail.
Keywords: sandwich cylindrical shells; FG coatings; clamped edges; hydrostatic buckling pressure; first order shear deformation theory; CONICAL SHELLS; STABILITY ANALYSIS; FGM; VIBRATION; PLATES; CORE; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering; Physics